Proceedings of the 11th International Conference on Intelligent User Interfaces 2006
DOI: 10.1145/1111449.1111533
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting kitchen appliances with a shared context using knowledge about daily events

Abstract: Networked appliances might make them aware of each other, but interacting with a complex network can be difficult in itself. KitchenSense is a sensor rich networked kitchen research platform that uses Common Sense reasoning to simplify control interfaces and augment interaction. The system's sensor net attempts to interpret people's intentions to create fail-soft support for safe, efficient and aesthetic activity. By considering embedded sensor data together with daily-event knowledge, a centrally-controlled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Several academic and research projects have investigated how smart objects can simplify complex tasks. For example, sensors and context awareness in kitchen utensils can help a user to prepare a meal [Lee et al 2006]. Intelligent technology and algorithms, such as hierarchical task networks and problem solving algorithms, provide a rich foundation for enabling objects to reason about complex tasks and compute on-thefly plans that can be used to guide the user.…”
Section: The Simplicity-featurism Paradoxmentioning
confidence: 99%
“…Several academic and research projects have investigated how smart objects can simplify complex tasks. For example, sensors and context awareness in kitchen utensils can help a user to prepare a meal [Lee et al 2006]. Intelligent technology and algorithms, such as hierarchical task networks and problem solving algorithms, provide a rich foundation for enabling objects to reason about complex tasks and compute on-thefly plans that can be used to guide the user.…”
Section: The Simplicity-featurism Paradoxmentioning
confidence: 99%
“…Recently Patel et al have shown that how residential power line events can be classified using machine learning algorithms to predict users' activities [11]. From commonsense-based system perspective, Lee et al presented augmented kitchen application where sensory data is overlaid with commonsense to assist user in kitchen activities [2]. In all these or similar works, recognition of the user activity using sensors is primarily used to provide contextual services.…”
Section: Related Workmentioning
confidence: 99%
“…Automating interaction sequence to improve user experience is an interesting research topic that has drawn significant attention in recent times. Specifically, the context-aware computing observes human activities and situational contexts to understand users intention to provide just-intime services [1,2,4,13]. However, instead of recognizing human activities entirely, our approach solely considers the operational states of artefacts and the correlation among them.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, ambient sensing systems are now embedded in homes and affixed to doors, beds [1], mattresses [2], toilets [3], wardrobes [4] and electrical appliances [5]. The wearable systems supported by ambient sensing have the capability to continuously monitor human physiology and dysfunction enabling critical events such as myocardial infarction, arrhythmias and strokes to be captured and consequently expediting treatments and saving lives [6].…”
Section: Introductionmentioning
confidence: 99%